Seasonality of carotenoid-based plumage coloration: Modelling wavelength-specific change through spectral reconstruction - Evans, SR; Summers, A; Sheldon, B (2012)
Plumage coloration has provided important model systems for research on signal expression. Whilst it had previously been assumed that moulting provided the only mechanism to change plumage coloration, recent studies have shown plumage colours to be seasonally dynamic, with implications both for the quantification of expression and for any signalling role. However, the mechanistic processes underlying such change remain uncertain. Here, we describe within-moult shifts in expression of a carotenoid-based colour trait - the yellow ventral plumage of the great tit Parus major - over a nine-month timespan. We report that plumage chromaticity ('colour') - but not achromaticity ('brightness') - exhibits a marked seasonal decline, independent of sex, age or body condition, and at a constant rate across twelve environmentally heterogeneous plots within our study site. To gain a greater understanding of the mechanisms underlying this change we employed a spectral reconstruction approach, that generates predicted spectra for any timepoint within the sampling period. By comparing spectra for both early and late in the moult we show that the seasonal decline in chromaticity is driven by both a marked reduction in ultraviolet (UV) reflectance and, to a lesser extent, loss of active carotenoid pigments. Thus, our study shows that seasonal loss of chromaticity in the great tit is driven by altered reflectance primarily in the UV section of the spectrum, a finding made possible by the use of spectral compartmentalisation and multi-parallel modelling to produce reconstructed spectra. Whether change in plumage coloration influences signal function will depend on the dynamics of the signalling system but it could clearly inflate patterns such as assortative mating and should be considered in studies of colour expression. © 2012 The Authors.